A Preventive Strategy Against Verbal Aggressive Behavior: Structured Learning Approach in Group Counseling - Ningrum, Baiq Nyi Diah Ridawan Husna; Setiyowati, Arbin Janu; Hambali, IM. (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Verbal aggressive behavior, including the use of abusive language, insults, threats, sarcasm, lies, defamation, and calling peers by offensive nicknames, is a persistent form of verbal violence that frequently occurs in school environments. This study aims to develop and empirically examine the effectiveness of a structured group counseling guide based on the Structured Learning Approach, presented in an e-book format, as a preventive intervention against verbal aggressive behavior among junior high school students. The research applied a development research method using the ADDIE model. The study involved 30 students as subjects for the effectiveness test and three experts (material, media, and user validators) for the validation process. Data were collected through expert judgment questionnaires, effectiveness measurement questionnaires, and documentation. Data analysis employed descriptive quantitative techniques supported by percentage calculations. The validation results indicated that the counseling guide possesses a very high level of validity in terms of relevance, usefulness, attractiveness, and ease of implementation. Additionally, the effectiveness test results revealed a significant decrease in students’ tendency to engage in verbal aggressive behavior after participating in group counseling sessions using the developed guide. This research concludes that the developed e-book-based group counseling guide is feasible and effective as a preventive strategy for fostering a safer, more positive, and harmonious school environment.